TRAINING AND MAINTENANCE OF DEVELOPMENT OF LEARNING DEVICES IN SD AND SMP GUPPI MEDAN-SUMATERA UTARA - Rita Suswati (VISION, 2017)
Community service program in the form of training and mentoring the preparation of learning tools, especially the making of learning media aims to improve the competence and performance of teachers MaPel in elementary and junior high school GUPPI Medan -Tembung. In addition, to provide knowledge and skills about the various learning media and the benefits of its use in class; namely to improve students' creativity and KKM. This activity is based on pre-existing observation of the location of dedication by UNIMED research team and agreement with school partners. The target object in this activity is the teachers of lessons in SD and SMP GUPPI Medan - Tembung consisting of 8 (eight) elementary teachers and 15 (fifteen) of junior high school teachers. Form of devotion done through workshops and mentoring the making of learning media and its use in the classroom through real teaching. Certificates and workshop materials are given to the trainees as training facilities and additional media in classroom learning activities. Through this activity, it is expected that teachers can improve their performance and implement the learning maximally with standard learning tools in accordance with the syllabus and curriculum used. Expected with improvements in teacher performance, students are also motivated to be more creative in the classroom and can achieve the required KKM scores.